Milk Yield and Quality of Etawah Cross Bred Goat Fed Legume based Diet with Urea Molasses Block and or Rice Bran Supplement at Early Lactation - Sukarini, IAM (ANIMAL PRODUCTION, 2006)
The current experiment aimed to determine milk yield and its quality of the Etawah cross bred goat fed with diet supplemented with urea molasses block (UMB) and or rice bran, were conducted for 8 weeks of early lactation period. Four lactating goats with average body weight of 44 kg were used and allocated into 4 dietary treatment groups in a Cross Over Design. Group A: basal diet (50% Gliricidia sepium leaves (GS) + 50% Hibiscus tilliacius leaves (HT)) as control; B: diet A + 75 g (2.58%) UMB; C: diet A + 500 g (14.44%) rice bran; and D: diet A+75 g (2.31%) UMB + 500g (14.33%) rice bran.  Each doe was subjected to all 4 treatments diet and every 2 weeks of rotation period of the treatment were given 4 days of rest.  The goats were hand milked twice daily following injection of oxytocin (0.5 I.U).  Daily milk yield was measured and aliquots of milk were taken for milk quality (chemical and physical) analysis.  Results showed that supplementation of urea molasses block and or rice bran on legume-based diet in early lactation significantly improved both milk yield and its quality (P<0.01).  The highest increament of milk yield was achieved by goat D, which was of 0.551 vs. 0.408 l/d compared to the control goat (A). Milk protein and milk dry matter were also highest in goat D which was 4.97 vs. 4.17% and 17.83 vs. 16.18% respectively. However, the highest milk fat content was obtained from goat C (5.46 vs. 5.05%) and the lowest was obtained from goat B (4.64 vs. 5.05%) compared to the control goat (A). (Animal Production 8(3): 196-205 (2006) Key Words : Etawah goat, urea molasses block, rice bran, milk quality